(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the theoretical and methodological foundations for researching the provision of personal security and inviolability in the context of digital technologies. It provides a socio-philosophical analysis of ensuring personal security and inviolability under digital conditions and examines the future tasks related to this issue. Additionally, the necessity and philosophical foundations of ensuring personal security and inviolability in modern society are analyzed.